Disorder and Weak Localization near Charge Neutral Point in Ti‐cleaned Single‐Layer Graphene. Issue 6 (20th February 2019) - Fujimoto, Akira; Perini, Christopher J.; Terasawa, Daiju; Fukuda, Akira; Harada, Yoshiyuki; Sasa, Shigehiko; Yano, Mitsuaki; Vogel, Eric M.
Abstract : The charge neutral point (CNP) for chemical‐vapor‐deposited (CVD) graphene appears at relatively high back‐gate voltages ( V G ) because of molecular adsorption and impurities on the graphene surface. Potential fluctuations due to these disorders strongly affect transport properties when the Fermi level approaches the Dirac point. In this work, a Ti‐cleaning process is used to shift the CNP of the transferred graphene surface to a lower V G . The effectiveness of charge doping due to Ti‐cleaning is also investigated through Raman scattering measurements. From the temperature dependence of the carrier concentration, the strength of the disorder potential for the CVD single‐layer graphene is estimated. The quadratic increase in the carrier concentration with temperature agrees with the theoretical prediction, which considers intrinsic thermal excitation combined with electron–hole puddles. Furthermore, based on weak localization (WL) analysis, the inelastic scattering length ( L ϕ ) decreases with temperature because of electron–electron interactions. The L ϕ also decreases near the CNP because of inhomogeneous charge distributions such as electron–hole puddles. Abstract : A Ti‐cleaning process is used to shift the charge neutral point of the transferred graphene surface to a lower back‐gate voltage. The effectiveness of charge doping due to Ti‐cleaning is also investigated through Raman scattering measurements. The quadratic increase in the carrier concentration with temperature agrees with the theoretical prediction, which considers intrinsic thermal excitation combined with electron–hole puddles.